REKONSTRUKSI PENGISIAN JABATAN KEMENTERIAN NEGARA DI INDONESIA MELALUI PERBANDINGAN DI NEGARA-NEGARA LAIN - ISTI ANJELINA MOHAMAD; ERMAN I. RAHIM; ABDUL HAMID TOME (GANEC SWARA, 2024)
The elected president appoints state ministers as a token of appreciation to the supporting coalition parties. The total percentage of post-reform for appointing state ministers from political party caolitions is 55,7%. In addition, the Indonesian Survey Institute (LSI) denotes that state ministers from professionals by 78,3% and from political parties or coalitions of political parties by 4.1%. specifically, this research was conducted using normative methods with a statue approach and a comparative approach. The research finding was obtained by comparing two parliamentary systems, namely the Netherlands and  England, and two presidential systems, namely the United States and South Korea. The appointment of state ministers in Indonesia post reform until now has main characteristics apparent in the appointment proves, namely the interest in coalition parties that have supported the party of the current elected president. Therefore, the ideal mechanism for appointing state ministers is to reconstruct Act Number 39 of 2008 concerning State Ministers, establish a special selection, team for ministerial appointments, the selection team proceeds with a sequence of selection, selection based on quality and integrity, and the appointment of state minister candidate by the president.